The Study of Waste Heat Recovery of the Thermal Management System of Electric Vehicle Based on Simulation and Experimental Analyses - Weiwei Lu; Qingxia Yang; Liyou Xu; Xiuqing Li (World Electric Vehicle Journal, 2025)
In this study, in order to overcome the limitations of existing electric vehicle (EV) thermal management systems (TMS), a highly integrated and coordinated operation strategy for EV thermal management was proposed. Specifically, an integrated architecture with a 10-way valve was established to replace traditional 3-way and 4-way valves to enhance the coupling between coolant circuits. Six operating modes were realized via the switching function of the 10-way valve, including the mode of waste heat recovery. A highly integrated TMS model was developed on the AMEsim2304 platform, followed by parameter matching. The accuracy of the model was validated through comparative analysis with laboratory and environmental chamber test results. Based on the designed highly integrated TMS, a classical fuzzy Proportional-Integral-Derivative Control (PID) control strategy was introduced to regulate the coolant circulation pump. Simulation analyses and experimental results demonstrated that the optimized system could reduce the battery pack heating time by approximately 300 s compared to the pre-optimized configuration. Moreover, the waste heat recovery could improve the cabin heating rate from 1.9 °C/min to 3.4 °C/min, representing a 43.7% enhancement. Furthermore, the output power of the high-pressure liquid heater remained low, resulting in a 10% reduction in overall heating energy consumption. Based on simulation and experimental analyses, this research can promote the progress of thermal management system technology for electric vehicles to a certain extent.